Iodine Status, Fluoride Exposure, and Thyroid Function in Pregnant Women in the United States. (14th June 2022) - Griebel-Thompson, Adrianne; Sands, Scott; Chollet-Hinton, Lynn; Christifano, Danielle; Sullivan, Debra; Hull, Holly; Carlson, Susan
Abstract: Objectives: Iodine (I) is an essential nutrient for fetal neurodevelopment through its role in thyroid function. Like I, fluoride (F) is a halogen and urinary F concentration (UFC) has been linked to increased thyroid stimulating hormone (TSH) in non-pregnant adults with I deficiency. We hypothesize that F and I may interact in their role on thyroid function among pregnant women. Methods: Pregnant women (n = 966) provided urine between 12- and 20-weeks gestation. UIC was measured by the modified Sandell-Kolthoff reaction and UFC by a F-sensitive electrode. Enzyme-linked immunosorbent assay (ELISA) was used to measure plasma TSH. Associations between 1) UIC and TSH, 2) UFC and TSH, and 3) I status, UFC, and TSH were estimated using generalized linear models with gamma distribution and log link. Potential interactions between I status and UFC in association with TSH was also investigated. Results: The cohort UIC (median: 154.2 µg/L, IQR: 92.9, 271.7) indicated a population with marginally adequate I status by WHO criteria. Nearly half (n = 464, 48%) were I insufficient (UIC ≤ 150 µg/L). Median UFC (0.832 mg/L, IQR: 0.495, 1.29) was above the benchmark used to determine risk for child cognition (0.2 mg/L) (Grandjean et al., Risk Anal 2021; doi: 10.1111/risa.13767). Higher UIC was associated with increased TSH (β = 0.0003, SE = 0.0001, p = 0.01). UFC was not related to TSH (p = 0.13); however, a significant interaction between UIC and UFC was observed (p = 0.01). When analyzing only I insufficient participants, UFC and TSH were inversely associated (β = 0.1488, p = 0.0004). No association between UFC and TSH was observed for I adequate participants (p = 0.63). Conclusions: Changes in TSH in relation to UIC and UFC were counter to our hypothesis as the relationship between UFC and TSH was inverse and only in I insufficient participants. Future research should explore if TSH is the best indicator of thyroid function in pregnancy and the mechanisms underlying the effects of pre-and postnatal F exposure on child cognition. Funding Sources: The Eunice Kennedy Shriver National Institute of Child Health and Human Development (NICHD) (R01 HD083292).